Surface modification of ultra‐high molecular weight polyethylene fibers by chromic acid. (5th May 2016) - Li, Weiwei; Meng, Li; Wang, Lun; Mu, Jingshan; Pan, Qiwei
Abstract : Ultra‐high molecular weight polyethylene (UHMWPE) fibers were modified by chromic acid. The effects of surface modification were evaluated with Fourier transform infrared spectroscopy (FTIR), X‐ray photoelectron spectroscopy (XPS), contact angle measurement, and scanning electron microscope (SEM). The results showed that both the content of O‐containing functional groups and surface roughness of modified fibers increased. The polar groups on the modified fiber surface decreased the contact angles with water and ethylene glycol, as evidenced by contact angle measurement. The tensile test results showed the strength and the elongation at break of UHMWPE fibers decreased but the modulus increased after chromic acid modification. Copyright © 2016 John Wiley & Sons, Ltd.